SURVEI KETERAMPILAN DASAR PADA PESERTA EKSTRAKURIKULER FUTSAL PUTRA SMK TAMTAMA KARANGANYAR - Hidayat, Muchtar Aji; Sumantri, Riyan Jaya (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2025)
Abstract: Futsal has become one of the most popular and widely played sports in Indonesia. Both urban and rural areas. However, it is predominantly played by teenagers and adults. The fundamental skills in futsal include several key techniques such as passing, controlling, and dribbling. This study aims to evaluate the basic futsal skills of extracurricular participants at SMK Tamtama Karanganyar in 2024. This research is a quantitative descriptive study with a single variable, without making comparisons or linking it to other variables. The sample consisted of 20 extracurricular participants selected using purposive sampling. The research method employed was a survey. The results showed that 2 participants (10%) were in the â€œExcellentâ€ category, 6 participants (30%) were in the â€œGoodâ€ category, 7 participants (35%) were in the â€œFairâ€ category, 4 participants (20%) were in the â€œPoorâ€ category, and 1 participant (5%) was in the â€œVery Poorâ€ category. The study concludes that most participants possess adequate basic futsal skills, although further development is needed to achieve higher proficiency.Keywords : Basic Skills, Futsal, Extracurricular, Vocational High School (SMK).Â Â Abstrak: Futsal cabang olahraga yang populer banyak diminati masyarakat Indonesia, mencakup berbagai usia, mulai dari anak-anak hingga orang dewasa, baik di perkotaan maupun pedesaan. Meskipun begitu, futsal lebih banyak dimainkan oleh kalangan remaja dan dewasa. Keterampilan dasar futsal mencakup beberapa teknik penting, antara lain teknik passing, controll, dan dribbling, Tujuan penelitian ini mengevaluasi keterampilan dasar futsal pada peserta ekstrakurikuler SMK Tamtama Karanganyar tahun 2024. Sampel terdiri dari 20 peserta ekstrakurikuler yang dipilih menggunakan teknik purposive sampling. Metode penelitian yang digunakan adalah survei. Hasil penelitian menunjukkan bahwa 2 peserta (10%) berada dalam kategori â€œBaik Sekaliâ€, 6 peserta (30%) dalam kategori â€œBaikâ€, 7 peserta (35%) dalam kategori â€œCukupâ€, 4 peserta (20%) dalam kategori â€œKurangâ€, dan 1 peserta (5%) dalam kategori â€œKurang Sekaliâ€. Penelitian ini menyimpulkan bahwa mayoritas peserta memiliki keterampilan dasar futsal yang cukup baik, namun masih diperlukan upaya pengembangan untuk mencapai keterampilan yang lebih tinggi.Kata kunci : Keterampilan Dasar, Futsal, Ekstrakurikuler, SMK.